New Approaches in Economic Sociology - Beckert, Jens (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The new economic sociology investigates the embeddedness of market activity in economic actors’ political, cultural and social environment. The exploration of markets from a sociological perspective stands at the foreground of this seminar, which is a sequel to Professor Streeck’s winter semester course. For this purpose, four major thematic areas will be highlighted: the cultural and political preconditions for the emergence of markets; the development of valuation in markets; the structuration of markets through institutions and networks; and the social conditions for overcoming possible barriers to market exchange.